Potensi Kearifan Lokal dalam Pendidikan Keaksaraan Fungsional pada Masyarakat Perdesaan di Kabupaten Jember - Indrianti, Deditiani Tri; Khutobah, Khutobah; Latif, Misno Abdul (Universitas Negeri Semarang, 2017)
The focus of the research study against the background of the condition that the rural community is the largest illiterate person in Jember regency. On the other hand, the implementation process of learning applied only introduce letters and numbers only. Therefore, need the right and basic way as a form of acceleration of illiteracy eradication that suits the needs of the community by exploiting the potential of local wisdom contained in the community. The system of functional literacy education resulting from this research activity is expected to be an applicative reference material for policy makers to reduce and solve illiteracy in Jember District, especially in rural communities. The research data collected in this research activity is primary and secondary, then analyzed by mix method (combining qualitative and quantitative data). Data collection was conducted with in-depth interviews and involved observations. The instruments used are structured interview guidelines through group discussions (Focus Group Discussions) and questionnaires. The results of the study found the potential of human resources and natural resources that can be developed in the activities of functional literacy programs. Where the local community order can influence in improving the economy of society.